Modelling Feasibility Scenarios for Achieving Public Space Standards in Nairobi's Informal Settlements under the 2030 Sustainable Development Framework - Odongo, Janes; Zhang, Boqian; Ma, Donghui (Pusbindiklatren Bappenas, 2025)
As the midpoint of the 2030 Sustainable Development Agenda nears, inclusive provision of public spaces in all urban neighbourhoods for all has become crucial. This study examines the progress towards delivering vital public spaces, namely streets, open spaces, and public markets in Nairobi's informal settlements, as a sustainable urbanism indicator. Based on the theories of sustainable development and sustainable urbanism, it uses a descriptive approach, relying on primary and secondary data from interviews with 17 key informants, questionnaires issued to 370 residents and street vendors, mapping of streets, markets, and open spaces using ArcGIS and Google Earth, and mathematical modelling to examine and describe local dynamics in Kayole Informal Settlement against public space prudential guidelines in global policy. Through the findings of this study that were cleaned, analyzed using SPSS, Excel, computations, and validated, the paper recommends alternative synergistic adjustments to policies, programs, and interactions to sustainably deliver functional public spaces, eradicate, and manage risks.